Frequency and risk factors of delirium in the pediatric intensive care unit of a tertiary care hospital: A prospective observational study - Sidra Khan; Abdul Haseeb; Muhammad Khalid; Atika Sher; Anwar Haque (Wolters Kluwer Medknow Publications, 2024)
Background: Critical illness is one of the most common causes of delirium in children which can be associated with increased morbidity and mortality. Delirium continues to be an overlooked aspect of the management of critically ill children. This study was conducted with the objective of determining the frequency and risk factors of delirium in critically ill children. Subjects and Methods: This prospective observational study included patients admitted for at least a period of 24 h of teaching in the pediatric intensive care unit (PICU) of a medical college of Pakistan from March 2022 to September 2022. Each patient was screened for developing delirium twice a day using the Cornell Assessment of Pediatric Delirium. Results: The median age of the patients was 19.5 months (interquartile range: 10.7-72). There were 64.6% (n = 106) of male children, and 97.2% (n = 143) were admitted due to medical conditions. Delirium was identified in 97 (59.1%) patients. Mortality was observed in 3 (1.8%) cases. The average length of stay and frequency of hypoxia was higher among the pediatric delirium group (P = 0.002 and P = 0.022, respectively). Independent predictors of delirium in PICU patients were length of stay (odds ratio [OR], 2.42; 95% confidence interval [CI], 1.39-4.20), use of inotropes (OR, 3.32; 95% CI, 1.0.4-10.64), use of narcotics (OR, 8.78; 95% CI, 0.96-80.51), and hypoxia (OR, 3.02; 95% CI, 1.17-7.81). Conclusion: Delirium is common in children admitted to PICU. Length of PICU stay, use of narcotics, inotropes, and hypoxia were found as independent risk factors for delirium.